2018
DOI: 10.1371/journal.pone.0198320
|View full text |Cite
|
Sign up to set email alerts
|

Hemodiafiltration is associated with reduced inflammation, oxidative stress and improved endothelial risk profile compared to high-flux hemodialysis in children

Abstract: Randomized trials in adults have shown reduced all-cause and cardiovascular mortality on hemodiafiltration (HDF) compared to high-flux hemodialysis (HD), but the mechanisms leading to improved outcomes are not clear. We studied biomarkers of inflammation, oxidative stress, anti-oxidant capacity and endothelial dysfunction in 22 children (13 female, age 8–15 years). All children received HD for at least 3 months, and were then switched to HDF, keeping all dialysis related parameters and dialysis time constant. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 41 publications
4
31
0
6
Order By: Relevance
“…According to a US Renal Data System report, 87.3% of incident patients with ESRD in the US used HD for RRT in 2016. The recent introduction of online-hemodiafiltration (OL-HDF) may offer major advantages in clearing molecules of various sizes, reducing HD-associated amyloidosis and chronic inflammation [5][6][7]. Because this modality has been officially approved for ESRD patients, the number of patients worldwide undergoing OL-HDF therapy doubled between 2004 and 2010, reaching 80,000 [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to a US Renal Data System report, 87.3% of incident patients with ESRD in the US used HD for RRT in 2016. The recent introduction of online-hemodiafiltration (OL-HDF) may offer major advantages in clearing molecules of various sizes, reducing HD-associated amyloidosis and chronic inflammation [5][6][7]. Because this modality has been officially approved for ESRD patients, the number of patients worldwide undergoing OL-HDF therapy doubled between 2004 and 2010, reaching 80,000 [8].…”
Section: Introductionmentioning
confidence: 99%
“…11 Even within a short period of 3 months on conventional hemodialysis (HD), biomarkers of inflammation, oxidative stress, and endothelial dysfunction were shown to increase. 12 Clearly, the sine qua non is prevention, but no studies in children have shown how to prevent the inexorable progression of CVD in patients on dialysis.…”
mentioning
confidence: 99%
“…In the case of ESRD, and especially dialysis, there are conflicting results on the levels of MMP-9 in the pre-and post-dialysis states [32,33]. This could be due to the different types of dialysis membranes [34,35], or to the type of dialysis itself [19,25]. We demonstrate herein that active MMP-9 is cleared during dialysis when the type of dialysis is not considered, but a decrease in active MMP-9 is only seen in HFD.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the type of dialysis used directly influences the oxidative status of the patients. Indeed, recent studies demonstrate that patients under OL-HDF have less inflammation, endothelial damage, and oxidative stress [19,24,25], which could be associated with the improved prognosis in this group [26,27]. The reduction in middle-molecules is associated with the preservation of residual renal function [28], which decreases the mortality risk in dialysis [29] and is improved in OL-HDF [30].…”
Section: Discussionmentioning
confidence: 99%